FAKTOR-FAKTOR YANG MEMPENGARUHI INITIAL RETURN PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Wiwien Djoko Prasetiyo, 15.05.52.0105; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of company size, auditor reputation, underwriter reputation, earnings per share, price earning ratio, financial leverage, company age, and the percentage of old shareholders on initial return on companies that carry out initial public offers (IPOs) on the Indonesia Stock Exchange during 2015-2018. The population used in this study consisted of all IPO companies during 2015-2018. So, the total population obtained is 125 data. After passing through the purposive sampling stage, a sample of 78 companies was obtained. The data analysis method used is descriptive statistics, normality test, classic assumption test, multiple linear regression test, model test and hypothesis test. The results of this study indicate that earnings per share has a negative effect on initial return. Whereas company size, auditor reputation, underwriter reputation, price earning ratio, financial leverage, company age and percentage of old shareholders has a negative effect and not significantly on initial return.